The effectiveness of strategy (K.W.L.H) in teaching the biography of the Prophet on the development of moral values ​​and awareness among elementary school students in Taif - Issa, Mohamed Ahmed; Al-Otaibi, Fatima Qasi Dhais (Journal of Educational and Psychological Sciences, 2018)
This study aims to identify the effectiveness of the strategy of KWL.H in teaching the prophetic biography on the development of moral values ​​and awareness among sixth grade pupils. The sample was divided into two groups: an experimental group of 20 students studied according to the KWLH strategy, and a control group of (20) female students studied according to the method. The results of the study showed the effectiveness of the KWLH strategy in the development of the moral values ​​identified in the study: generosity, vulnerability, benevolence, uterine bonding, compassion, and animal welfare. ), While the control obtained an average of (10,72), as well as its effectiveness in developing awareness (28,20) compared to (12.80) for the control group. The study also revealed that there is a correlation between the commitment to the moral values ​​(0.84) and awareness (0.66). In light of the results of the study, a number of recommendations and proposals were presented.